Prevalence of root fusion in canine maxillary second molar teeth using cone-beam computed tomography - Linder, Kristin; MacGee, Scott; Schultz, Loren (Frontiers in Veterinary Science, 2023)
This study evaluated the prevalence of root fusion in the right and left maxillary second molar teeth 110 and 210 in dogs using cone-beam computed tomography (CBCT). A total of 180 patient dog CBCT scans, or a total of 360 maxillary second molar teeth, were analyzed in this study. Patients Dogs were divided into weight categories of small (<10kg), medium (10kg -25kg), and large (>25kg). Skull type (brachycephalic, mesocephalic, dolichocephalic) and sex were also recorded for each patientdog. Overall, 65% of maxillary second molar teeths displayed had some type of root fusion. Of the teeth that displayed had fusion, the only configuration represented was fusion of the distobuccal root with the palatal root. The most common root morphology overall (all patients dogs and both left and rightright and left maxillary second molar teeth included) was partial fusion (177/360, 49%). With the high prevalence of fused roots in maxillary second molar teeths in dogs found in this study, CBCT will help clinicians to more accurately assess a dogpatient's anatomy and implications for treatment.